ANTIBACTERIAL ACTIVITY FOR MULTI DRUG RESISTANCE (MDR) BACTERIA BYSEA CUCUMBER Stichopus vastus EXTRACT FROM KARIMUNJAWA ISLANDS – INDONESIA - Delianis Pringgenies; Ali Ridlo; Nerva Sembiring (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
The study aims to explore the antibacterial activity of Stichopus vastus against pathogenic MDR bacteria. Analysis of samples of sea cucumbers included extraction, fractionation, and analysis of bacterial sensitivity test Gas Chromatography-Mass Spectrometry (GC-MS), the extraction process is carried out by solid-liquid extraction method. Fractionation was done with Open-Column Chromatography (OCC). Sensitivity test of bacteria was done using an agar diffusion method according to the Kirby-Bauer (Ref). The study revealed that from 5 species MDR bacteria, which are Coagulant negative stapylococi (CNS), E. coli, Enterobacter 5, Klebsiella sp. dan Pseudomonas sp. There are two MDR bacteria had the most sensitive responses by the extract of sea cucumber, which were Enterobacter-5 and Klebsiella sp. The two bacteria were tested against five bioactive fractions obtained from OCC. Fraction criteria-2 had the highest antibacterial activity against Enterobacter-5 and Klebsiella sp, with serial concentration of 20 µg ∙ disc–1, 40 µg. disc–1 and 80 µg. disc–1. Largest inhibition zone were obtained from 80 µg. disc–1 againts the two bacteria were (14.73 ± 0.48) mm and (11.22 ± 0.85) mm respectively. GC-MS Analysis revealed that fraction criteria-2 had (or consisted of) cyclohexhane, ethanol, butanoic and pentanoic acids. Keywords: antibacterial activity, multi drug resistance (MDR), sea cucumber, Stichopus vastus